INFLUENCE OF METEOROLOGICAL PARAMETERS ON PM₂.₅ AND ASSOCIATED AIR POLLUTION EPISODES IN KARAGANDA, CENTRAL KAZAKHSTAN (2017–2024) (Eurasian Journal of Ecology, 2026)
Karaganda, one of the most heavily polluted industrial cities worldwide, experiences severe air quality challenges due to emissions from coal mining, metallurgical industry and coal-fired power plants. This study investigates the influence of meteorological parameters on PM₂.₅ concentrations and associated air pollution episodes in Karaganda, Central Kazakhstan, using a monthly dataset spanning 2017–2024. The meteorological parameters including temperature (°C), relative humidity (%), atmospheric pressure (hPa), wind speed (m/s) and pollutant concentrations including suspended particulate matter (dust, mg/m³), PM₂.₅ (mg/m³), PM₁₀ (mg/m³), sulfur dioxide (SO₂, mg/m³), carbon monoxide (CO, mg/m³), nitrogen dioxide (NO₂, mg/m³), ozone (O₃, mg/m³), ammonia (NH₃, mg/m³), and formaldehyde (HCHO, mg/m³) were analyzed to explore meteorology-driven variability in air pollution. Time series analyses and correlation assessments were conducted, and three complementary regression approaches, Multiple Linear Regression (MLR), Random Forest Regression, and Gradient Boosting via LightGBM were applied to robustly characterize the relationships between meteorological conditions and PM₂.₅ levels. Results indicate persistently high pollution levels, with exceedances of daily average concentrations observed for PM₂.₅, PM₁₀, dust, phenol, formaldehyde, and ozone, with PM₂.₅ showing the most pronounced exceedances. Air pollution episodes were particularly severe during the cold season, driven by emissions from thermal power plants and residential heating. Multi-year trends revealed increasing occurrences of high-concentration events, primarily due to PM₂.₅, PM₁₀, SO₂, and CO, highlighting the significant contribution of industrial and energy-related emissions to the urban atmosphere. Meteorological conditions, particularly calm or low-wind periods (0–3 m/s), further exacerbated pollutant accumulation during episode periods, with 106 such days recorded in 2024 alone. These findings underscore the critical role of both emission sources and weather conditions in shaping air quality in Karaganda and provide a basis for targeted mitigation strategies.Key words:  Karaganda, PM₂.₅, meteorological parameters, air pollution episodes